Petrological study of monogenetic volcanoes in the fore-arc region of the northern Kamchatka Peninsula - Nishizawa T.; Churikova T.G.; Gordeychik B.N.; Ishizuka O.; Nakamura H.; Iwamori H. (Tokyo Institute of Technology, 2014)
The western part of the Pacific Plate is subducting under the Okhotsk Plate along Kuril-Kamchatka Trench, and the northern part of it is subducting under the Bering Sea Plate with high obliquity along the western Aleutians arc. The three plates form the Aleutian-Kamchatka triple junction [l]. The northern edge of the Pacific Plate is separated from Bering Sea Plate by transform fault, and the mantle edge beneath the Kamchatka Peninsula is thought to be open towards the Bering Sea.